2021
DOI: 10.1080/10717544.2021.1923863
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-loaded polymeric nanoparticles based on α-tocopheryl succinate for the treatment of head and neck squamous cell carcinoma: in vivo murine model

Abstract: Paclitaxel-loaded polymeric nanoparticles based on α-tocopheryl succinate for the treatment of head and neck squamous cell carcinoma:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The results showed that under the action of drug release from drug-loaded implants, these five osteosarcoma cells exhibited different degrees of apoptosis, with all of them being mainly late-stage apoptosis. This was consistent with the apoptosis of PTX alone as well as with the results of previous studies on the action mechanism of PTX [ 14 , 48 ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The results showed that under the action of drug release from drug-loaded implants, these five osteosarcoma cells exhibited different degrees of apoptosis, with all of them being mainly late-stage apoptosis. This was consistent with the apoptosis of PTX alone as well as with the results of previous studies on the action mechanism of PTX [ 14 , 48 ].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Sunitinib has been found to exert immunomodulatory properties by increasing the invasion of lymphocytes and DCs into the tumour milieu, while reducing the number and activity of T regs and bone marrow-derived suppressor cells [ 565 ]. Nanoparticles can also be used to deliver immunostimulant agents for effective tumour immunotherapy, providing a smart new vehicle for the efficient presentation of tumour antigens and adjuvants on antigen-presenting cells [ 566 , 567 , 568 ]. An example is the use of the tandem peptide nanocomplex (TPNC) carrying CpG DNA ligand of TLR9s (iTPNC), which inhibits tumour growth in animal models of various cancers.…”
Section: Resultsmentioning
confidence: 99%
“…To improve its therapeutic value, a polymeric nanodrug system was developed to target the transmission of PTX. This system displayed higher efficacy and fewer adverse reactions than free PTX in a HNSCC mouse xenograft model ( 26 ). Future research is required to provide more extensive evidence of the application of PTX-NPs in HNSCC patients.…”
Section: Nanotherapy In Hnsccmentioning
confidence: 99%